Recent Developments in Laser Welding of Aluminum Alloys to Steel - Wallerstein Daniel; Salminen Antti; Lusquiños Fernando; Comesaña Rafael; Val García Jesús del; Rodríguez Antonio Riveiro; Badaoui Aida; Pou Juan (MDPI, 2022)
The development of high-performance dissimilar aluminum-steel joints is necessary to promote the feasibility of multi-material design and lightweight manufacturing. However, joining aluminum to steel is a challenging task mainly due to the formation of brittle intermetallic compounds (IMC) at the joint interface. Laser welding is considered a very promising joining process for dissimilar materials, although its application in industry is still limited by the insufficient mechanical performance of the joints. The present paper aims to give a comprehensive review of relevant recent research work on laser joining of aluminum to steel, contributing to highlighting the latest achievements that could boost acceptance of laser joining of dissimilar materials by the modern industries. To this end, the most important challenges in laser joining of aluminum to steel are presented, followed by recent approaches to overcome these challenges, the state-of-art of comprehension of IMC formation and growth, and the different strategies to minimize them.